Association of Stress and Musculoskeletal Pain With Poor Sleep: Cross-Sectional Study Among 3,600 Hospital Workers - Vinstrup, Jonas; Jakobsen, Markus Due; Calatayud, Joaquin; Jay, Kenneth; Andersen, Lars Louis (Frontiers in Neurology, 2018)
Background While acute stress and pain are part of our inherent survival mechanisms, persistent stress and pain can negatively impact health and well-being. This may also lead to poor sleep and thus a lack of recovery. This study investigated the influence of stress and musculoskeletal pain on sleep quality. Methods A total of 3,600 Danish hospital workers replied to a questionnaire about work and health. Pain intensity was evaluated using subjective values as an average of 9 body parts. Stress was assessed using the full version of Cohen´s Perceived Stress scale. Sleep quality was rated using 3 questions on sleep characteristics. Associations between stress and pain (mutually adjusted predictors) and sleep (outcome) were modelled using binary logistic regression controlling for gender, age, education, BMI and smoking. Results The risk ratio of moderate stress (compared to no/low stress) on poor sleep was 1.27 (CI 1.26-1.29), whereas the risk ratio of high stress on poor sleep was 1.87 (CI 1.83-1.91). Similarly, for pain, the risk ratio of moderate pain (compared to no/low pain) on poor sleep was 1.18 (95% CI 1.16-1.19), whereas the risk ratio of a high pain score on poor sleep was 1.48 (95% CI 1.44-1.52). Conclusion This study demonstrates that both stress and musculoskeletal pain are associated with poor sleep among hospital workers. Hospital management should consider implementing strategies for preventing stress and musculoskeletal pain to improve the overall health and workability among hospital workers.